Impacts of a concentrated solar power trough facility on birds and other wildlife in South Africa. (4th May 2019) - Jeal, Corey; Perold, Vonica; Ralston-Paton, Samantha; Ryan, Peter G
Abstract : This study assesses bird and wildlife mortality and changes in bird species communities at a 50 MW utility-scale concentrated solar power parabolic trough facility in South Africa. The facility was searched for evidence of large vertebrate mortalities over three months. Eight bird carcasses were recorded in the solar field, all of which probably died prior to the study period. Carcass persistence trials indicated that 94% of bird carcasses survived 24 h, 68% for 7 d, and 56% for 28 d, although persistence varied with carcass size. No large carcasses (>1 000 g) were removed entirely by scavengers after 28 d, whereas only 42% of medium-sized (100–1 000 g) and 17% of small (<100 g) carcasses remained after 28 d. Searchers detected 72% of bird carcasses, with large birds more likely to be detected than small birds. The extrapolated mortality rate for the facility was 3.9 birds y −1 (90% CI 0.0–14.9) or 0.1 bird fatalitites MW y −1 (90% CI 0.0–0.3). Birds were much more abundant (141.9 birds km −1 ) and species rich (51 species) in the surrounding rangeland than in the solar field (1.27 birds km −1 ; 22 species). Of the 24 bird carcasses found in the evaporation ponds, six likely drowned (four species). Three reptiles (one species) and 12 mammals (seven species), including sensitive species such as aardvark Orycteropus afer, also drowned in the evaporation ponds. This is the first study of its kind in South Africa and unexpectedly revealed that the evaporation ponds had a bigger impact on wildlife than anticipated.